The Use of Infographics as a Systemic Functional Approach to Improve Students' Understanding of Shakespeare's Drama - Putri Rindu Kinasih; Magdalena Kartikasari Tandy Rerung; Vallen Mutiara Halim (SALEE: Study of Applied Linguistics and English Education, 2023)
Despite its importance, it should be noted that teaching literature, especially in an EFL setting, can be challenging. Numerous studies have been conducted to examine various literature on teaching methods for EFL students. The strategies used in the research, however, heavily rely on teachers' attempts to spoon-feed students' understanding. Thus, in this research, the writers aim to study students’ perceptions of using infographics in studying intrinsic elements in Shakespeare’s drama. This study adopts the mixed-method approach. The participants of this study are 71 students from the second semester consisting of 41 females, and 30 males majoring in English Language and Literature (BBI) at UBM University. The result of the questionnaire was analyzed by using SPSS. In addition to processing the questionnaire results, the writers also conduct a semi-structured interview to gather additional perspectives and in-depth insights about the usage of infographics to improve students' comprehension of Shakespeare's play. This study concludes that participants were eager to learn fundamental aspects of Shakespeare's drama through infographics. Students' short attention spans and Shakespeare's difficult language can both be overcome with the use of infographics.